KINERJA TUTOR PENDIDIKAN KESETARAAN DI PKBM SE-KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Siti Munawaroh; Said Suhil Achmad; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the level of performance of equality education tutors in PKBM in Rumbai Pesisir Subdistrict, Pekanbaru City, the most dominant dimension to the performance of equality education tutors in PKBM in Pekanbaru City Rumbai Pesisir District and Performance Variation of equality education tutors in PKBM Pekanbaru City's Rumbai Pesisir District is based on gender, age and level of education. The type of research in this study is descriptive research with a quantitative approach. The population in this study were all equality education tutors in PKBM in Rumbai Pesisir Subdistrict, Pekanbaru City, amounting to 38 people. The sampling technique in this study uses a non-probability sampling technique using a saturated sampling technique in which all members of the population are sampled. The instrument in this study was a questionnaire containing statements about the performance of equality education tutors in PKBM in the District of Pekanbaru's Coastal Tassel. Variable instruments in the form of questionnaires using a Likert scale consisting of five answer choices. From the research findings, it can be seen that the performance level of equality education tutors in PKBM in the District of Rumbai Pesisir, Pekanbaru, is good, this can be seen from the Mean 4.26 and Standard Deviation (SD) 0.51 from the average indicator of the research. Furthermore, viewed from the more dominant dimensions are Quantity dimensions with Mean values of 4.29 and Standard Deviation (SD) 0.52. The ANOVA results on variations in the performance of equality education tutors in PKBM in the Districts of Pekanbaru's Rumbai Pesisir, based on gender, age, and education level, can be seen that there is no variation. Key Words: Performance, Tutor, Equality Education, PKBM